AN AGRICULTURAL PRODUCTION AS A SIGNFICANT AREA OF A STATEGY OF ECONOMY DIPLOMACY OF SERBIA - Nešković, Slobodan (Economics of Agriculture, 2012)
Contemporary trends and objective circumstances in the global level condition a need for changes and adaptation of social and political systems, so as human abilities would be used in an optimal way. Economy diplomacy as the main aim of its functioning positions an international approach in promotion of all positive values of a country, where affirmation of our agricultural products represents an essential possibility and chance in the world market. Cuurent international challenges implicate the essential position of a man and having made a personality of a business diplomat, capable to implement reforms in all levels of management. The contemporary world is being faced with huge issues in securing production of enough quantities of healthy safe food, especially of animal origin. A number of factors directly, but also indirectly, endanger the health of people through food. Vet management of livestock health and production related to the increase of milk industry and public is to improve two areas in the livestock production, and these are safety of food and animals beneft. A strategic approach of the Republic of Serbia involves all relevant subjects of the country, especially economy diplomats who represent and affrm Serbian national, and production resources, frstly.